Financial Stability of Insurance Companies in Selected CEE Countries - Pavić Kramarić Tomislava; Miletić Marko; Kožul Blaževski Renata (Business Systems Research, 2019)
Background: Financial stability or soundness of insurance companies has gained importance over the years, especially after the financial crisis of 2008. Various stakeholders such as policy makers, regulators, the insured, etc. are interested in keeping the insurance sector stable since it contributes to overall financial stability.